Dialektika Manusia dan Agama - Muh. Yunus (UIN Maulana Malik Ibrahim Malang, 1999)
The existence and role of religion (Islam) get a sharp criticism, which essentially needs a re-examination of religious dogma that has been frozen, if religion does not want to be abandoned by the swift stream of modernization. Truly the religion God revealed to the earth is for man. So religion is born to man, not man born to religion. If man is born to religion, then the most prominent is his transcendent dimension, the religious world from which he came, far from the earth. If so, then humans enter into the world aIkoholistik-theocentric, intoxicated. Factors that cause humans away from the ideal message of the Qur'an is a factor understanding of religion. A series of worship conducted by religious people such as prayer, zakat, fasting, pilgrimage, and the like only stop at the point of carrying out obligations (fiqh oriented) and become a symbol of piety, while the fruits of worship that dimensi sosial less visible. Among religious communities, there has been a misunderstanding in interpreting and appreciating and appreciating the symbolic message. As a result, religion is understood only as an individual savior and not as a social blessing. Eksistensi dan peran agama (Islam) mendapatkan kritik tajam, yang intinya perlu adanya pengkajian ulang terhadap dogma agama yang selama ini telah membeku, jika agama tidak ingin ditinggalkan begitu saja oleh derasnya arus modernisasi. Sesungguhnya agama itu diturunkan Tuhan ke bumi memang untuk manusia. Jadi agama lahir untuk manusia, bukan manusia lahir untuk agama. Jika manusia lahir untuk agama, maka yang paling menonjol adalah dimensi transendennya, dunia agama tempat asal ia turun, jauh dari bumi. Jika demikian, maka manusia masuk kedalam dunia aIkoholistik-teosentris, mabuk ketuhanan. Faktor yang menyebabkan manusia jauh dari pesan ideal al Quran adalah faktor pemahaman terhadap agama. Serangkaian ibadah yang dilakukan umat beragama (Islam) seperti shalat, zakat, puasa, haji, dan sejenisnya hanya berhenti pada sebatas menjalankan kewajiban (fiqh oriented) dan menjadi simbol kesalehan, sedangkan buah ibadah yang berdimensi sosial kurang nampak. Di kalangan masyarakat beragama, telah terjadi kesalahpahaman dalam memaknai dan menghayati serta mengapresiasi pesan simbolik itu. Akibatnya, agama hanya di pahami sebagai penyelamat individu dan bukan sebagai keberkahan sosial.